10-Year Incidence of Diabetic Ketoacidosis at Type 1 Diabetes Diagnosis in Children Aged Less Than 16 Years From a Large Regional Center (Hangzhou, China) - Peng, Wei; Yuan, Jinna; Chiavaroli, Valentina; Dong, Guanping; Huang, Ke; Wu, Wei; Ullah, Rahim; Jin, Binghan; Lin, Hu; Derraik, José G. B.; Fu, Junfen (Frontiers in Endocrinology, 2021)
Background Diabetic ketoacidosis (DKA) is a potentially life-threatening complication of type 1 diabetes (T1D), and a leading cause of death in children aged <15 years with new-onset T1D. Aims i) to assess the incidence of DKA in children and adolescents newly diagnosed with T1D over a 10-year period at a large regional center in China; and ii) to examine the clinical symptoms and demographic factors associated with DKA and its severity at diagnosis. Methods We carried out a retrospective audit of a regional center, encompassing all youth aged <16 years diagnosed with T1D in 2009–2018 at the Children’s Hospital, Zhejiang University School of Medicine (Hangzhou, China). DKA and its severity were classified according to ISPAD 2018 guidelines. Results 681 children were diagnosed with T1D, 50.1% having DKA at presentation (36.0% mild, 30.0% moderate, and 33.9% severe DKA). The number of patients diagnosed with T1D progressively rose from approximately 39 cases/year in 2009–2010 to 95 cases/year in 2017–2018 (≈2.5-fold increase), rising primarily among children aged 5–9 years. DKA incidence was unchanged but variable (44.8% to 56.8%). At T1D diagnosis, 89% of patients reported polyuria and 91% polydipsia. Children presenting with DKA were more likely to report vomiting, abdominal pain, and particularly fatigue. DKA was most common among the youngest children, affecting 4 in 5 children aged <2 years (81.4%), in comparison to 53.3%, 42.7%, and 49.3% of patients aged 2–4, 5–9, and ≥10 years, respectively. Children with severe DKA were more likely to report vomiting, fatigue, and abdominal pain, but less likely to report polyuria, polydipsia, and polyphagia than those with mild/moderate DKA. Rates of severe DKA were highest in children aged <2 years (51.1%). Conclusions The number of children diagnosed with T1D at our regional center increased over the study period, but DKA rates were unchanged. With 9 of 10 children reporting polyuria and polydipsia prior to T1D diagnosis, increasing awareness of this condition in the community and among primary care physicians could lead to earlier diagnosis, and thus potentially reduce rates of DKA at presentation.